Topography, disturbance and climate: subalpine forest change 1972-2013, Rocky Mountain National Park, USA - Esser, Scott M., author; Sibold, Jason S., advisor; Bobowski, Ben, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2015)
Many forest tree species are expected to migrate in order to track suitable habitat due to changing climate (Stohlgren et al. 2000, Holzinger et al. 2007, Bell et al. 2013). Changes in climate will likely alter important fine-scale ecological factors such as water balance or microsite conditions which are vital for vegetation (Dobrowski 2011). Species distribution models suggest that many species should have already begun to migrate to track apposite climate (Rehfeldt et al. 2006, Littell et al. 2010, Monahan et al. 2013). While these models are a good starting point, they do not incorporate many variables that are critical for understanding forest changes and migration such as fine-scale topography and disturbance (Pearson and Dawson 2003). I resampled 68 subalpine forest plots originally surveyed in 1972-73 in Rocky Mountain National Park (RMNP) to investigate changes in species composition and structure and assess species migration during the past 40 years. I specifically considered forest change and migration in the context of topography, disturbance and climate. Data indicate species composition has remained relatively stable, with new species arriving in only 13% of plots. Forest structure has changed, shifting toward greater abundance of large-diameter trees with a reduction in small-diameter trees. Total stem densities decreased on south-facing slopes, increased on north-facing slopes, and remained stable at low elevations and increased at higher elevations. Species migration has been predominantly upslope on south-facing slopes while species elevations remained stable across north-facing slopes. These findings suggest that climate change has impacted forests of RMNP during the past 40 years. Impacts to vegetation have been mediated by topographic position and disturbance, demonstrating the importance of these factors in altering climate change impacts at the microsite scale. Northern aspects appear to be more buffered from the impacts of warming temperatures than southern aspects and these areas may become potential refugia in the future. Further understanding of the interactions among topography, disturbance and climate is vital for anticipating how forests could change and this information will lead to better ecosystem management and preservation of biodiversity in the future.